IL-17A mediates inflammation-related retinal pigment epithelial cells injury via ERK signaling pathway - Hui-Min Zhong; Bing-Qiao Shen; Yu-Hong Chen; Xiao-Huan Zhao; Xiao-Xu Huang; Min-Wen Zhou; Xiao-Dong Sun (International Journal of Ophthalmology)
AIM: To investigate whether interleukin-17A (IL-17A) gets involved in the mechanisms of inflammation-related retinal pigment epithelium (RPE) cells injury and its significance in age-related macular degeneration (AMD). RESULTS: In the scenario of NaIO3 stimulation, RPE cells obviously tended to degenerate. Simultaneously proliferation and activation of retinal microglia was confirmed in NaIO3-stimulated mice, whereas such effects induced by NaIO3 were significantly ameliorated with IL-17A NAb intervention or in IL-17A-/- mice. In addition, IL-17A promoted the proliferation and activation of microglia as well as oxidative damage and the secretion of inflammatory cytokines alongside NaIO3-induced damage in RPE cells in vivo and ex vivo. Meanwhile, the extracellular signal-regulated kinase (ERK) signaling pathway was shown to be participated in the regulation of NaIO3-induced RPE cells injury mediated by IL-17A in vivo and ex vivo, as IL-17A-induced inflammatory cytokines release in the NaIO3 model was alleviated after blocking the ERK pathway. CONCLUSION: IL-17A probably promotes the NaIO3-induced RPE cells injury through exacerbating inflammation in terms of retinal microglia activation and inflammatory cytokines release via ERK signaling pathway. Inhibition of IL-17A may be a new potential target for dry AMD treatment.